2006
DOI: 10.1002/fam.940
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gypsum board type (X or C) on real fire performance of partition assemblies

Abstract: SUMMARYThis paper compares the responses of wall-size partition assemblies, composed of either type X or type C gypsum wallboard panels over steel studs, when each was exposed to an intense room fire. The exposures lasted from the time of ignition to beyond flashover. Heat flux gauges provided time histories of the energy incident on the partitions, while thermocouples provided data on the propagation of heat through the partitions and on the progress toward perforation. Visual and infrared cameras were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 9 publications
4
56
0
2
Order By: Relevance
“…In this case, the remaining gypsum plasterboard does not benefit from the heat absorbed due to the decomposition of Calcium Carbonate (Equation 3). Manzello et al [5] reported that an exothermic reaction where soluble crystal changes to lower insoluble energy state occurs at about 400ºC as shown in Equation 4, which was not stated by other researchers.…”
Section: Introductionmentioning
confidence: 72%
“…In this case, the remaining gypsum plasterboard does not benefit from the heat absorbed due to the decomposition of Calcium Carbonate (Equation 3). Manzello et al [5] reported that an exothermic reaction where soluble crystal changes to lower insoluble energy state occurs at about 400ºC as shown in Equation 4, which was not stated by other researchers.…”
Section: Introductionmentioning
confidence: 72%
“…Due to its thermal properties, the plaster is perceived as a hygroscopic material, which allows the regulation of the microclimate in the room [29,30]. is plaster is vapor-permeable, does not close the water in the construction, and at the same time allows the natural drying of residual water from the blocks.…”
Section: Plastermentioning
confidence: 99%
“…In PCM micro-encapsulation, the PCM is enclosed in thin sealed polymer spherical capsules, ranging in size from 1 m to 300 m, which can maintain their shape and prevent leakage during the phase change process [9]. In commercially available products, the solid-liquid phase change occurs in the typical indoor temperature ranges (20)(21)(22)(23)(24)(25)(26) • C), and it is favourable for building energy consumption purposes. However, in a fire event, building materials may be exposed to substantially higher temperatures, that may reach 800 • C; in this case, there is a high possibility for leakage, which would allow PCM vapours to be directly exposed to the fire environment [5,10].…”
Section: Use Of Phase Change Materials In Buildingsmentioning
confidence: 99%
“…In this context, the performed simulations are used to investigate the fire resistance of the utilized GP wall assemblies. GP exposed to fire are considered to exhibit mechanical failure when cracks or openings are observed through the wall [20]; however, since cracking phenomena cannot be accurately simulated in the FDS code, alternative failure criteria are used in this study. According to the Eurocode standards [21], fire safety regulations regarding the "integrity" of a compartment wall assembly specify that the maximum temperature rise at the unexposed side (ambient facing side) should not exceed 180 • C. In the current simulations, the ambient temperature was considered to be 20 • C; therefore, the aforementioned "failure" criterion for a GP wall assembly corresponds to a temperature of 200 • C on its unexposed side.…”
Section: Application In a Large Scale Fire Compartment-façade Arrangementioning
confidence: 99%